Towards better comprehension of the theory by enhancing languaging in engineering mathematics course differential calculus - Rinneheimo, Kirsi-Maria; Joutsenlahti, Jorma (FMSERA Journal, 2020)
This paper introduces the use of languaging exercises in the engineering mathematics course ´Differential Calculus´. Mathematical exercises are typically seen as expressible by symbols and expressions. Languaging exercises are expressed by natural language, by pictures, or by a combination of these. In this paper it is demonstrated how the languaging exercises were utilized to clarify and deepen the learning of the theory. The study aimed at enhancing the understanding of theory by exploiting languaging exercises. Studies conducted among the university students have shown that using languaging exercises develops students’ mathematical understanding. The findings indicate that among the students who studied in the group where the languaging exercises were used got better exam results in the exercises related to understanding the theory.